An investigation of intrinsic and extrinsic motivation towards the level of employees' job satisfaction at Ibu Pejabat Jabatan Bomba Dan Penyelamat Malaysia Negeri Pahang (JBPM Negeri Pahang) / Hanun Hamzah - Hamzah, Hanun (Faculty Of Business Management, 2016)
The study was conducted in order to identify the relationship between employee motivation and job satisfaction. There are two types of motivation which are extrinsic motivation and intrinsic motivation. According to the previous researchers, motivations depend on the employees' job satisfactions. If employees do not feel motivated, they will not feel fully satisfied with their jobs. The instrument used to conduct this survey was by distributing the questionnaires. The questionnaires were distributed to eighty (80) respondents in Ibu Pejabat Jabatan Bomba dan Penyelamat Malaysia Negeri Pahang (JBPM Negeri Pahang) by using the simple random sampling technique. The findings of the data are clearly shows that's the mean of the employees at Ibu Pejabat Jabatan Bomba dan Penyelamat Malaysia Negeri Pahang (JBPM Negeri Pahang) is moderately high and there is significant relationships between motivational factors and employee's job satisfaction. Therefore the alternate hypothesis is accepted. It can be concluded that the majority of the respondents at in Ibu Pejabat Jabatan Bomba dan Penyelamat Malaysia Negeri Pahang (JBPM Negeri Pahang) is male and were married. Most of the respondents were Diploma holder and age between 28 years old to 35 years old and have 6 to 10 years working experience with most of them held lower management position. The findings show that among the motivation factors, the most influential factor that affects employees is self-interest. Self-interest can be described as a passion toward the responsible tasks, willingly to do the work without any stress or pressure Therefore, after the data were collected and analyzed, the researcher suggested the recommendation for the organization is to increase the monetary rewards in order to motivate the employees to perform the work efficiently. The recommendation for future research is to focus more on adding the population size in order to get more valid and concrete data. Other than that, the instruments should be varied.